In situ structure and assembly of the ABC-type tripartite pump MacAB-TolC - Tong Huo; Wenfang Zhang; Zhili Yu; Wei Zheng; Yaoming Wu; Qiuyu Ren; Zekai Wan; Junli Cao; Zhao Wang; Xiaodong Shi (Communications Biology)
Abstract The MacAB-TolC tripartite efflux pump is widely distributed in Gram-negative bacteria, extruding antibiotics and virulence factors that lead to multidrug resistance and pathogenicity. However, the in situ structure and assembly mechanism of MacAB-TolC remain unclear. Here, we resolve the in situ structures of the MacAB-TolC efflux pump in Escherichia coli by electron cryo-tomography and subtomogram averaging. In the cells without antibiotic treatment, we observe a fully assembled MacAB-TolC pump. When Escherichia coli cells are treated with erythromycin, in addition to the tripartite pumps, we also discover the emergence of MacA-TolC subcomplexes without MacB, indicating flexible binding of MacB in the presence of an antibiotic substrate, which is further validated by in vivo photo-crosslinking results. Together, our data suggest the in situ assembly process of MacAB-TolC starts from the formation of MacA-TolC subcomplex, and provides insights into the design of efflux pump inhibitors.